Building Pâris' Beden Seyad: a replica of the Omani 19th‐century sewn fishing vessel. (1st September 2019) - Ghidoni, Alessandro
Abstract: The beden seyad is a simple yet elegant Omani sewn fishing craft documented by the French naval officer François‐Edmond Pâris during his visit in Oman in 1838–1839. A 10m‐long scaled‐down replica of the vessel was built by a team of experts in a traditional boatyard in Qantab, the Sultanate of Oman, and is displayed in the Maritime History Gallery at the National Museum of Oman. This article describes different aspects of the building process of the vessel, from the material used to the method of construction. It compares the different versions of the beden drawing provided by Pâris and discusses the decision‐making and problem‐solving procedures carried out by the construction team.